Introgression of Two Broad-Spectrum Late Blight Resistance Genes, Rpi-Blb1 and Rpi-Blb3, From Solanum bulbocastanum Dun Plus Race-Specific R Genes Into Potato Pre-breeding Lines - Rakosy-Tican, Elena; Thieme, Ramona; König, Janine; Nachtigall, Marion; Hammann, Thilo; Denes, Tunde-Eva; Kruppa, Klaudia; Molnár-Láng, Márta (Frontiers in Plant Science, 2020)
There is a wealth of resistance genes in the Mexican wild species of Solanum, but very few of these species are sexually compatible with cultivated Solanum tuberosum. The most devastating disease of potato is late blight caused by the oomycete Phytophthora infestans (Pi). The wild hexaploid species S. demissum, which it is possible to cross with potato, was used to transfer eleven race-specific genes by introgressive hybridization that were subsequently widely used in potato breeding. However, there are now more virulent races of Pi that can overcome all of these genes. The most sustainable strategy for protecting potatoes from late blight is to pyramid or stack broad-spectrum resistance genes into the cultivars. Recently four broad-spectrum genes (Rpi) conferring resistance to Pi were identified and cloned from the sexually incompatible species S. bulbocastanum: Rpi-blb1 (RB), Rpi-blb2, Rpi-blb3 and Rpi-bt1. For this research a resistant S. bulbocastanum accession was selected carrying the genes Rpi-blb1 and Rpi-blb3 together with race-specific R3a and R3b genes. This accession was previously used to produce a large number of somatic hybrids (SHs) with five commercial potato cultivars using protoplast electrofusion. In this study three SHs with cv. 'Delikat' were selected and backcross generations: BC1 and BC2 were obtained using cvs. 'Baltica', 'Quarta', 'Romanze' and 'Sarpo Mira'. Their assessment using gene-specific markers demonstrates that these genes are present in the SHs and their BC progenies. Plants carrying all the genes and resistant to foliage blight in a greenhouse and the field were identified. Functionality of the genes was shown by using agro-infiltration with the effectors of corresponding Avr genes. For a number of hybrids and BC clones yield and tuber number in field trials were not significantly different from that of the parent cultivar ‘Delikat’. The evaluation of agronomic traits of selected BC2 clones and of their processing qualities resulted in valuable material for breeding late blight durable resistant potato. This is an efficient way of combining somatic hybridization with the additional use of gene specific markers and corresponding Avr effectors for successful identification and introgression of late blight resistance genes into potato gene pool.